2020
DOI: 10.1038/s41598-020-60543-z
|View full text |Cite
|
Sign up to set email alerts
|

Drone Surveys Do Not Increase Colony-wide Flight Behaviour at Waterbird Nesting Sites, But Sensitivity Varies Among Species

Abstract: Aerial surveys can also disturb nesting colonial waterbirds, sometimes causing severe panic responses, nest abandonment, and delayed return times to the nest 13-15. It is common for birds to look up, scan more, or remain vigilant during aircraft overflights 16. Furthermore, prolonged vigilance can divert time and energy away from activities that are needed to increase individual fitness 17,18. However, some mixed-species nesting colonies are not significantly affected by aerial surveys, behaviourally or reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Negative reactions to drones have been evaluated in several marine species of different taxa, which were present in a few species in marine environments. Most of these reactions were recorded in birds during the breeding season in species highly sensitive to disturbance and sometimes with an intense territorial behavior [16,18]. During breeding, other studies have suggested that breeders react to flying movements rather than sound disturbance [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative reactions to drones have been evaluated in several marine species of different taxa, which were present in a few species in marine environments. Most of these reactions were recorded in birds during the breeding season in species highly sensitive to disturbance and sometimes with an intense territorial behavior [16,18]. During breeding, other studies have suggested that breeders react to flying movements rather than sound disturbance [33].…”
Section: Discussionmentioning
confidence: 99%
“…Several reactions have been recorded in wildlife in response to drones; some species ignore the presence of UAVs completely [16], and others react by evading [17] or confronting them, attacking the flying device in their territories aggressively [18]. Urban and semi-urban are the most utilized areas for UAVs because of the high density human population and connectivity facilities.…”
Section: Introductionmentioning
confidence: 99%
“…Ground‐based surveys, especially those in which an airboat is involved, would likely encourage broods to seek refuge in nearby escape cover, therefore hindering the survey. Unmanned aerial vehicles have been used to survey broods across a variety of landscapes (Pöysä et al 2018) and cause little disturbance to breeding birds (Barr et al 2020). Additionally, unmanned aerial vehicles equipped with thermal‐imaging cameras allow researchers to identify the presence of broods even when in dense vegetative cover.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is an area of growing research. Several studies have anecdotally evaluated behavior, but it has not been until recent years that controlled studies focused on behavior have been conducted (Barnas et al 2018b;Barr et al 2020;Egan et al 2020). A review of behavioral studies by Mulero-Pázmány et al (2017) concluded that there are many factors that impact behavioral responses of wildlife which include species, life history characteristics, drone platform characteristics, altitude, and flight approaches (at angles vs. directly at animals).…”
Section: Introductionmentioning
confidence: 99%